Patient-Level DNA Damage Repair Pathway Profiles and Anti-Tumor Immunity for Gastric Cancer - Lou, Shenghan; Wang, Yufei; Zhang, Jian; Yin, Xin; Zhang, Yao; Wang, Yimin; Xue, Yingwei (Frontiers in Immunology, 2022)
DNA damage repair (DDR) comprises the detection and correction of alterations in the chemical structure of DNA. The dysfunction of the DDR process has been determined to have important implications for tumor carcinogenesis, malignancy progression, treatment resistance, and prognosis assessment. However, the role of the DDR process in gastric cancer (GC) remains to be fully understood. Thus, a total of 2,019 GC samples from our hospital (Harbin Medical University Cancer Hospital in china) and 12 public data sets were included in our study. In this study, single-sample gene set enrichment analysis (ssGSEA) was used to generate the DDR pathway activity profiles of 8 DDR sub-pathways and identify a DDR pathway signature by combining the DDR sub-pathway gene sets. The DDR pathway profiling's impacts on the clinical outcomes, biological functions, genetic variants, immune heterogeneity, and treatment responses were analyzed through multidimensional genomics and clinical data. The results demonstrate that the DDR pathway profiling was clearly distinguished between tumor and normal tissues. The DDR pathway profiling reveals patient-level variations, which may contribute to explaining the high heterogeneity of human GC for the biological features and treatment outcomes. Thus, tumors with low DDR signature scores were independently correlated with shorter overall survival time and significantly associated with mesenchymal, invasion, and metastasis phenotypes. The statistical model integrating this DDR pathway signature with other clinical predictors outperforms each predictor alone for predicting overall survival in discrimination, calibration, and net clinical benefit. Moreover, low DDR signature scores were tightly associated with genome stability, characterized by low tumor mutational burden (TMB) and low fractions of genome alteration. Furthermore, this study confirms that patients with low DDR pathway signature scores might not benefit from adjuvant chemotherapy and a monoclonal antibody directed against programmed cell death-1 ligand 1 (anti-PD1) therapy. These findings highlighted that the DDR pathway profiling confers important implications for patients with GC and provides insights into the specific clinical and molecular features underlying the DDR process, which may help to facilitate clinical management.